Quantification Of The Impact Of Climate Change In Financial Reports: An Ambition Towards Net Zero Emissions - Insirat, Mutahira Nur; Puspitasari, Ningsih; Sunarti, Sunarti; Lestari, Belinda; Indrayani, Hesti; Muchran, Muchriana (Jurnal Penelitian IPTEKS, 2024)
Climate change is one of the big problems facing the world. The special report on Global Warming of 1.5°C shows that achieving zero emissions by mid-century is an important thing to do. The importance of addressing climate change drove global cooperation that led to the signing of the Paris Agreement in 2015. Closing the gap between current climate change mitigation policies and the policies needed to achieve the Paris Agreement temperature targets requires a significant increase in policy ambition. This article argues that policy actions aimed at achieving zero emission levels can be carried out by setting an effective carbon price, the relevance and materiality of climate change issues in financial reports, as well as knowing the strategy for quantifying climate change issues in financial reports based on applicable SAK.